Microballoon pressure sensors for particle imaging manometry in liquid and gaseous media. Issue 4 (26th January 2016) - Banerjee, N.; Mastrangelo, C. H.
Abstract : We present the fabrication and testing of engineered microballoon particles that expand and contract under external pressure changes hence serving as microscopic pressure sensors. Abstract : We present the fabrication and testing of engineered microballoon particles that expand and contract under external pressure changes hence serving as microscopic pressure sensors. The particles consist of 12 μm hollow flexible 0.4 μm-thick parylene-C shells with and without a coating of ultrathin Al2 O3 diffusion barriers, and the changes in the particle radius are measured from the particle spectral reflectivity. The microballoons display radial pressure sensitivities of 0.64 nm psi −1 and 0.44 nm psi −1, respectively in agreement with theoretical estimates. The microballoon devices were used for mapping the internal pressure drop within microfluidic chips. These devices experience nearly spherical symmetry which could make them potential flow-through sensors for the augmentation of particle-based flow characterization methodologies extending today's capabilities of particle imaging velocimetry.